Peruvian university students’ mental health in crisis: assessing anxiety, depression, fear, and stress during the Russia-Ukraine conflict - Jeel Moya-Salazar; Jeel Moya-Salazar; Eliane A. Goicochea-Palomino; Víctor Rojas-Zumaran; María Jesús Moya-Salazar; María Jesús Moya-Salazar; Gloría Cruz-Gonzales; Hans Contreras-Pulache (Frontiers in Public Health)
BackgroundThe conflict between Russia and Ukraine, exacerbated by the COVID-19 pandemic, has created global fears over the possibility of another third world war. Populations both close to and far from the conflict can be affected by it and the mental health outcomes can be devastating. We aimed to assess levels of anxiety, depression, fear, and stress among Peruvian university students facing potential war-related consequences.MethodsThis web-based observational study conducted in 2022 included 494 randomly selected students. Participants were over 18 years of age, with a balanced representation of gender and geography. Anxiety, depression, stress, and fear of war were evaluated using validated instruments, including the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9).ResultsOf the participants, 58.3% were women, with an average age of 26.4 ± 8.1 years. Symptoms of stress, fear, anxiety, and depression affected 49.2, 49, 47.8, and 47.8%, respectively. Women were more affected, with 54.2% reporting high stress and 53.5% reporting high fear (p < 0.001). The most vulnerable group for anxiety and depression were younger students aged 18–20, with 44.3% presenting mild anxiety and 44.3% mild depression (p < 0.001).ConclusionThese findings highlight the urgent need for mental health interventions for university students, particularly women and younger students, who face heightened vulnerability to global crises such as wars and pandemics. Further studies should explore additional influencing factors, including pre-existing health conditions, academic challenges, and regional disparities, to address these mental health issues better.